ANALISIS PENGARUH KREATIVITAS IKLAN TERHADAP KEPUTUSAN PEMBELIAN KARTU SELULER AS DENGAN CELEBRITY ENDORSER SEBAGAI VARIABEL MODERASI (Survei pada Mahasiswa S1 Universitas Slamet Riyadi Surakarta) - Endah Andayani, Rahayu Triastity & Erni Widajanti (Universitas Slamet Riyadi, 2016)
The objective of the research are to analyses (1) the effect of advertising creativity to the purchase decision As mobile card on S1 students University of Slamet Riyadi Surakarta (2) the effect of celebrity endorser on purchase decisions As mobile card on S1 students University of Slamet Riyadi Surakarta (3) the effect of advertising creativity on purchasing decisions As cellular card in moderation the celebrity endorser at the University of S1 students Slamet Riyadi Surakarta. Population of this research is a mobile card users on S1 students University of Slamet Riyadi Surakarta as the use of As mobile card and seen the advertisement “selamat pagi ayam” and taken a sample of 70 respondents. Data collection technique used questionnaire that through stages of testing the validity dan reliability test. Test requirements regression using classic assumption test. Data were analyzed using absolute difference test. The conclusion of each hypothesis test results show that (1) advertising creativity does not have a significant effect on purchase decision As mobile card on S1 students University of Slamet Riyadi Surakarta, is shown by p value 0,842 > 0,05. (2) celebrity endorser have a significant effect on purchase decision As mobile card on S1 students University of Slamet Riyadi Surakarta, is shown by p value 0,015 < 0,05. (3) celebrity endorser does not moderate the effect of advertising creativity on purchase decisions As mobile card on S1 student University of Slamet Riyadi Surakarta , it is shown by p value 0,073 > 0,05 .Keywords: advertising creativity, celebrity endorser, purchase decision.